Private Equity Premium Puzzle Revisited - Kartashova, Katya (American Economic Review, 2014)
This paper revisits the results of Moskowitz and Vissing-Jørgensen (2002) on returns to entrepreneurial investments in the United States. Following the authors' methodology and new data from the Survey of Consumer Finances, I find that the “private equity premium puzzle” does not survive the period of high public equity returns in the 1990s. The difference between private and public equity returns is positive and large period-by-period between 1999 and 2007. Whereas in the 2008–2010 period, overlapping with the Great Recession, public and private equities performances are substantially closer. I validate these results in the aggregate data going back to the 1960s. (JEL G11, G12, L26)